Islam in the United States of America: By Sulayman S. Nyang. Chicago: ABC International Group, Inc., 1999. 165 pp. (American Journal of Islam and Society, 2000)
Although Islam is the youngest of the three Abrahamic religions, it bas succeededin making breakthroughs in all comers of the globe. Today, it is thefastest growing religion in the world. and its presence has become a recognizedfact in rich industrialized nations like the United States. In the book underreview, Professor Sulayman Nyang examines the arrival and development ofIslam in America and asserts that it will stand permanently side-by-side withChristianity and Judaism and that these religions will co-exist peacefully.In the first chapter. the author tells the story of the African Muslim slaves inNorth America. The discovery of the New World by Columbus resulted in thetransplantation of millions of African slaves to work in the plantations of whitesettler farmers. A large number of slaves were captured in West Africa - aregion where Islam had already become firmly rooted. However, the nature of slavery itself (as it was practiced in America) and the separation of the childrenfrom their Muslim parents impeded the take-off process of Islam in America.These were also critical times for the African Muslim slaves, as they were notallowed to practice their religion freely. This lack of religious tolerance forcedmany of the slaves to convert to Christianity, which was the faith of their "masters."The author also mentions the wave of Muslim immigrants that occurredduring the frrst quarter of the twentieth century and involved people from theMiddle East, North Africa, southern and central Asia, and southern and centralEurope. Some of these immigrants returned home after the war, but manydecided to stay in the United States in order to pursue the American Dream.The next turning point for Islam was the Islamic Revolution, which broke outin Iran in 1979 and had a very strong impact in the United States due to thecountry's close alliance with the ousted Shah ...